A COMPARATIVE STUDY OF ZAKAT FINANCIAL MANAGEMENT IN SUDAN, GAZA, AND INDONESIA (International Conference on Social and Islamic Studies, 2022)
The effectiveness of zakat in poverty reduction has become controversial. Some belief it to be highly effective and some believe that its effectiveness has decreased than in the time of the apostle Prayer of God. Most of them are considered to be less effective in our time, so the researcher decided to do a study in this area, especially in Zakat systems in some Arab countries. Zakat systems in Islamic countries are very different from each other have different zakat systems, Which made us ask which of these systems is the best for managing and distributing the financial of zakat, To reduce or alleviate poverty, at a time when the number of poor Muslims is increasing which has made the researcher deeper into understanding this problem and how to solve it, In three different countries selected as examples to deepen their zakat systems, Information for this study has been collected from books, research, documents, records, judgments, and others. Information that demonstrates the scientific answers to each of the research questions is then extracted, and the researcher may get that each of these three systems is commensurate with the nature of the country, the census, and even the problems experienced by each country individually. However, there seems to be a lack of distribution of zakat funds and the (Muzaki) themselves, making zakat a 100% ineffective tool, but much less, and even the numbers of the poor increase in each of these three countries (Gaza and Indonesia), All three systems are effective in managing the finances of zakat in certain proportions, but they have some shortcomings, making them unable to eradicate poverty or even reduce the number of poor people. This makes them need to be more disciplined in other respects, such as collecting and distributing zakat funds by legitimate means, and weakens them in a challenge to do awareness-raising or forcing them to pay zakat of all kinds.